Faktor Penyebab Rendahnya Partisipasi Remaja dalam Kegiatan Keagamaan sebagai Problematika PAI di Desa Janti Jogoroto Jombang - Leila Aisya Bella; Emi Lilawati; M. Aliyul Wafa (Lembaga Yasin AlSys, 2026)
Although adolescent participation in community-based religious activities has received attention in various previous studies, research that specifically discusses the causes of low participation as a direct problem of Islamic Religious Education (PAI) in the context of rural Java remains limited. This study aims to analyze the factors causing low adolescent participation in religious activities and to explain how these factors become fundamental problems for PAI in Janti Jogoroto Village, Jombang. This study used a qualitative approach with a phenomenological design, involving 12 informants consisting of adolescents, parents, and religious figures selected using purposive sampling. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and verification. The results showed that low adolescent participation was caused by a combination of internal factors, such as low interest, laziness, lack of self-confidence, shyness, and fatigue due to school or work, as well as external factors, such as strong peer influence, social media distractions, monotonous activities, and limited access to facilities. These factors become problems for PAI because they indicate a gap between cognitive understanding and religious practice, weak internalization of Islamic values, and the incompatibility of conventional PAI approaches with the developmental characteristics of adolescents. These findings contribute to the development of nonformal PAI studies by integrating Ajzen’s Theory of Planned Behavior and Durkheim’s functionalism, and expand understanding of the role of socio-digital factors in mediating religious education outcomes in rural communities. The conclusion of this study emphasizes that low adolescent participation plays an important role in weakening the sustainability of communal religious traditions, so parents, religious figures, PAI teachers, village governments, and religious institutions need to design mentoring strategies that are more collaborative, empowering for adolescents, and adaptive to digital development.